Senecio piedrahitae (Compositae, Senecioneae), a new species from the Colombian Andes - Calvo, Joel; Ávila, Fabio (Phytotaxa, 2016)
A new species of Senecio gr. Lasiocephalus from the Central Andes of Colombia is described. It is a scandent subshrub recognized by its lanceolate leaves, clearly petiolated the middle cauline ones, asymetrical at the lamina base, floccose above and lanate beneath, by its synflorescence branches densely lanate, and glabrescent or slightly arachnoid involucre. It is known from the páramos of the volcanic complex Tolima-Santa Isabel-Ruiz. The morphologically closest taxon is S. otophorus var. christophori.